Analisis Kualitas Website e-RKAM Menggunakan Metode WebQual 4.0 - Febriyani, Risa; Syafrianto, Syafrianto (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2025)
Technological developments in the field of education have encouraged the implementation of the e-RKAM application to facilitate the preparation and reporting of School Operational Assistance funds digitally in madrasas. However, there are still some technical obstacles such as servers that often go down, errors in some menus, and delays in producing the latest report output (update), which has a significant impact on the quality of application services. This study aims to analyze the quality of the e-RKAM website using the WebQual 4.0 method, which includes three variables: usability quality, information quality, and service interaction quality, as well as its influence on user satisfaction. The results of the analysis showed that these variables together contributed 44.7% to user satisfaction, while the remaining 55.3% was influenced by other factors outside this study. The T-test showed that only the quality of information had a significant influence on user satisfaction (sig. value 0.000), while the quality of usability and the quality-of-service interaction had no significant effect (sig. values of 0.066 and 0.844, respectively). These findings highlight that the model used has not been fully comprehensive in explaining the variation in user satisfaction, so more research is needed to explore additional factors that may have an effect.